MODERN METHODS OF DIAGNOSTICS OF LYSOSOMAL STORAGE DISEASES - Konarbayeva, A.; Tarlykov, P.V. (Eurasian Journal of Applied Biotechnology, 2026)
Lysosomal storage diseases, such as Gaucher, Niemann-Pick, Pompe, Krabbe, Fabry, and Mucopolysaccharidoses, are a group of more than 50 rare inherited metabolic diseases caused by dysfunction of lysosomes due to deficiency of specific enzymes. The early and accurate diagnosis of lysosomal storage diseases is important for the correct drug administration, genetic counseling, and prevention of severe complications. In Kazakhstan, the diagnosis of lysosomal storage diseases is difficult due to limited laboratory capabilities and low prevalence of these diseases among the population. This review discusses modern diagnostic methods, including tandem mass spectrometry, next-generation sequencing, and enzymatic activity tests. For forehanded diagnosis of lysosomal storage diseases, it is important to integrate molecular, genetic, and biochemical diagnostic methods, as well as develop national newborn screening programs.